2015
DOI: 10.1186/s13104-015-1329-z
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection by hydrogen peroxide nebulization increases susceptibility to avian pathogenic Escherichia coli

Abstract: BackgroundAvian pathogenic Escherichia coli (APEC) are the major cause of economic losses in the poultry industry worldwide. Traditionally, antibiotics are used to treat and prevent colibacillosis in broilers. Due to resistance development other ways of preventing/treating the disease have to be found. Therefore during this study the nebulization of low concentrations of hydrogen peroxide (H2O2) was tested in the presence of chickens to lower pathogenicity of APEC.ResultsSignificantly higher total lesion score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 12 publications
(12 reference statements)
0
21
0
Order By: Relevance
“…However, H 2 O 2 is a highly reactive oxidizing agent and has genotoxic effects. Oosterik et al (45) reported that nebulization of 2% H 2 O 2 renders chickens more susceptible to avian pathogenic E. coli, potentially due to epithelial damage by hydroxyl radicals. The simultaneous use of L-histidine may decrease the H 2 O 2 concentration necessary to eradicate Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, H 2 O 2 is a highly reactive oxidizing agent and has genotoxic effects. Oosterik et al (45) reported that nebulization of 2% H 2 O 2 renders chickens more susceptible to avian pathogenic E. coli, potentially due to epithelial damage by hydroxyl radicals. The simultaneous use of L-histidine may decrease the H 2 O 2 concentration necessary to eradicate Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…During the title and abstract screening, 2,234 records were excluded as not complying with the inclusion criteria (96.8%), while 74 records passed to the full text screening phase. Ultimately, only 4 studies were included as fitting the inclusion criteria ( Oosterik et al, 2015 ; Gholami-Ahangaran et al, 2016 ; Li et al, 2018 ; Graham et al, 2021 ).
Figure 1 Flow diagram according to PRISMA guidelines showing the selection process for the systematic review on biosecurity to prevent or control colibacillosis in broiler production.
…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies included, 3 were randomized controlled trials ( RCTs ) in which animals were challenged with E. coli ( Oosterik et al, 2015 ; Li et al, 2018 ; Graham et al, 2021 ), and one was a RCT with natural disease exposure ( Gholami-Ahangaran et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations